Pengetahuan Masyarakat Terhadap Tanaman Obat Keluarga (TOGA) di Kelurahan Pemurus Luar : Pengetahuan Masyarakat Terhadap Tanaman Obat Keluarga (TOGA) di Kelurahan Pemurus Luar - Ghina Zhahera; Melviani Melviani; Kunti Nastiti (LPPM Universitas Sari Mulia, 2023)
Background: The development of knowledge in the medical field that gave birth to various types of drugs containing chemicals, public confidence in the ability of herbal medicines is decreasing. One of the factors that causes the loss of public confidence in the efficacy of traditional medicines is the loss of knowledge about traditional medicines owned by the ancestors of the Indonesian nation. Knowledge about this family medicinal plant needs to be continuously developed so that the process of creating knowledge continues among the community groups that develop it. Objective: To know the public's knowledge of Family Medicinal Plants (TOGA). Methods: Descriptive research with Univariate analysis. Sampling with purvosive sampling technique. The sample of the study was 97 respondents. data obtained from questionnaires distributed to the public. Results: Community knowledge on the types of family medicinal plants 49% in good category, about the benefits of family medicinal plants 84% ​​in good category, about processing methods for family medicinal plants 45% in good category, and community on how to use family medicinal plants 48% quite good category. The use of family medicinal plants in the community there are 27 family medicinal plants. Conclusion: Public knowledge of family medicinal plants in Pemurus Luar Village is on average with good knowledge. Keywords : Knowledge, Family Medicinal Plants